Anglicismos y formaciones derivadas en español actual - Rodríguez González, Félix (2021)
The object of this article is twofold: on the first hand, to give an account of the enormous and growing number of derivatives formed from Anglicisms in present-day European Spanish; and secondly, to examine the different derivational patterns found as well as the morphophonological, morphological and semantic variations involved in them. The article also tackles the lexicographic treatment followed in dictionaries when dealing with compound anglicisms. The data have been mainly drawn from the Spanish daily press of the last few decades and they are mostly part of those collected in the Gran diccionario de anglicismos, GDA (2017) and in the recent Diccionario de anglicismos del deporte, DAD (2021).